Blood pressure measurement practices in children and adolescents within primary care setting - Čeponytė, Kamilė; Ažukaitis, Karolis; Jankauskienė, Augustina (Frontiers in Pediatrics, 2025)
ObjectivePoor compliance to the technical aspects of blood pressure (BP) measurement procedure may lead to inaccurate estimation of BP and misclassification of patients. However, the latter have not been explored systematically. We aimed to assess real-life BP measurement practices in Lithuanian children and adolescents at the primary care setting, and their compliance with current European Society of Hypertension (ESH) guidelines.MethodsTwo cross-sectional surveys were conducted in Lithuania. The study population included parents, who have children aged 0–17 years, and was further enriched by adolescents aged 14–17 years. Original questionnaires were developed and used to survey the participants.ResultsStudy included 1,504 parents and 448 adolescents. Median age of the surveyed parents' children and adolescents was 6 years and 50.2 percent were female. Overall, among all children aged 3 years or older only 55% of respondents reported BP measurements at least once. The rates of BP measurements increased with age and exceeded 80 percent from 14 years. Only 3.3 percent of respondents reported no issues with BP measurement procedure. The most common errors included single measurements of BP (81.4%), lack of feedback (60.2%), incorrect positioning (40.7%), miscuffing (39.2%) and lack of rest period (27.9%).ConclusionsOur study reveals not only insufficient BP screening rates within Lithuanian primary care setting, but also high rates of technical errors during BP measurement procedure. Collectively, these issues likely contribute to misdiagnosing of arterial hypertension and suboptimal care of children who are at risk of inaccurate and imprecise BP results.